Rescue therapy with Sofosbuvir /Velpatasvir/ Voxilaprevir in a patient infected with Hepatitis C virus multidrug resistant variant—a much needed option for DAA-treatment failures in Pakistan? A case-report - Arif, Ambreen; Qureshi, Huma (Journal of the Pakistan Medical Association, 2024)
Primary non-response to the currently available direct acting anti-viral (DAAs) in chronic hepatitis C virus (HCV) is rare and expected in approximately only 3-4% of the patients. Among the plausible explanations, HCV resistant variant may be one of the causes among the several other viral and host factors implicated in cases who do not achieve cure. Ever since the approval of licensed DAAs in 2014, focus has been mainly on high cure rates. Hence, significantly less attention has been given to the few difficult to treat cases. We present, herein, the case of a 50-year old male who had previously failed to respond to the currently available first and second-line DAA treatment and was then approved for a special treatment access programme. According to our knowledge this is the first case-report from Pakistan in favour of the physician’s directive for special treatment access for HCV DAA-experienced patients. Keywords: Hepatitis C virus, Direct acting anti-virals, Standard of care, Pakistan.